Solve for y 6.1=y+3.6

Math
6.1=y+3.6
Rewrite the equation as y+3.6=6.1.
y+3.6=6.1
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 3.6 from both sides of the equation.
y=6.1-3.6
Subtract 3.6 from 6.1.
y=2.5
y=2.5
Solve for y 6.1=y+3.6

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top